Implications of the Application of Critical Race Theory to Racial Inequality and Racism in Indonesia - Herdiawan Herdiawan; Nur Laila Ramadhani; Alziqry Arifin; Rafifah Aqila Wafa Kaulika; Elviandri Elviandri (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
This study begins with the understanding that race is not a biological entity but rather a social construct shaped by history, politics, and power relations. The research method used is qualitative with a historical approach through a literature study of primary and secondary legal sources related to the development of Critical Race Theory (CRT). The results of the study show that the history of CRT has succeeded in exposing the issue of skin color differences that have been used to justify the positions of those in power, who have always been considered to favor white people. Even though society is required to think rationally in relation to organizations and institutions, certain groups are still being discriminated against today. CRT has provided the principle that exploring the structure of liberal principles must be gradual and objective. Based on this principle, CRT can reveal power structures that are often alienated and have a racial character towards American society. Thus, through these principles, CRT has great potential to understand the situation of practices that disadvantage certain groups, such as in education, the legal system, or citizens' rights in accessing life in their country. The implication of applying CRT to race and racism in Indonesia, with its ethnic and cultural diversity, is that injustice is not merely personal, but rather that inequality arises from those who hold power in this regard, such as social, economic, and political structures. Thus, CRT has exposed the structures of inequality and offered a new perspective on racial differences and racism in Indonesia.